Effects of ascent to high altitude on human antimycobacterial immunity. - Sarah Eisen; Louise Pealing; Robert W Aldridge; Mark J Siedner; Alejandro Necochea; Inna Leybell; Teresa Valencia; Beatriz Herrera; Siouxsie Wiles; Jon S Friedland; Robert H Gilman; Carlton A Evans (PLoS ONE)
Background Tuberculosis infection, disease and mortality are all less common at high than low altitude and ascent to high altitude was historically recommended for treatment. The immunological and mycobacterial mechanisms underlying the association between altitude and tuberculosis are unclear. We studied the effects of altitude on mycobacteria and antimycobacterial immunity. Methods Antimycobacterial immunity was assayed in 15 healthy adults residing at low altitude before and after they ascended to 3400 meters; and in 47 long-term high-altitude residents. Antimycobacterial immunity was assessed as the extent to which participants' whole blood supported or restricted growth of genetically modified luminescent Bacille Calmette-Guérin (BCG) mycobacteria during 96 hours incubation. We developed a simplified whole blood assay that could be used by a technician in a low-technology setting. We used this to compare mycobacterial growth in participants' whole blood versus positive-control culture broth and versus negative-control plasma. Results Measurements of mycobacterial luminescence predicted the number of mycobacterial colonies cultured six weeks later. At low altitude, mycobacteria grew in blood at similar rates to positive-control culture broth whereas ascent to high altitude was associated with restriction (p ≤ 0.002) of mycobacterial growth to be 4-times less than in culture broth. At low altitude, mycobacteria grew in blood 25-times more than negative-control plasma whereas ascent to high altitude was associated with restriction (p ≤ 0.01) of mycobacterial growth to be only 6-times more than in plasma. There was no evidence of differences in antimycobacterial immunity at high altitude between people who had recently ascended to high altitude versus long-term high-altitude residents. Conclusions An assay of luminescent mycobacterial growth in whole blood was adapted and found to be feasible in low-resource settings. This demonstrated that ascent to or residence at high altitude was associated with decreased mycobacterial growth in whole blood relative to controls, consistent with altitude-related augmentation of antimycobacterial cellular immunity.